Limb-Sparing Using Total Hip Arthroplasty in a Dog with Femoral Head Osteosarcoma - Kawamoto, Fernando Yoiti Kitamura; Zeponi, Aflailton; dos Santos Júnior, Wanderley Severo; de Faria, Luís Guilherme; Franco, Guilherme Galhardo; Minto, Bruno Watanabe (Acta Scientiae Veterinariae, 2017)
Background: Osteosarcoma (OSA) is the most common primary bone tumor of the appendicular skeleton of dogs. It mainly affects the metaphyseal region of long bones in large and giant breed dogs.The markedly aggressive and metastatic character of the disease leads to an invariably poor to unfavorable prognosis.Although amputation is commonly performed, different surgical techniques may be used to preserve the limb. The most common methods of limb preserving surgeries involve the use of endoprosthesis and allogeneic or autologous grafts. This report describes the successful use of total hip replacement to treat a 3-year-old male dog, with OSA in the femoral head and neck. Case: This report describes the successful use of total hip replacement to treat a 3-year-old male dog, with OSA in the femoral head and neck. The OSA stage IA located in the femoral head and neck was resected and treated through the limb-sparing. The bone defect and joint function was reconstructed with total hip arthroplasty technique using a cementless hip prosthesis. The result of the histopathological analysis of the excised bone tissue showed a minimally productive osteoblastic osteosarcoma. To date, the patient shows satisfactory movement rate and motion range, with no pain to palpation and without lameness in that limb. The radiographic follow-up after 24 months showed no local recurrence, metastasis pulmonary or complications related to the implant. Total hip arthroplasty resulted in safe recovery of orthopedic signs associated with osteosarcoma of the femoral head and neck, effectively acting as a limb preserving surgery after 32 months. Discussion: The limb-sparing procedure is an option to control local tumors that has become more popular among owners that do not accept the amputation of the limb. Similarly, it is a good alternative when another condition may interfere with the other limbs or may require amputation of another limb. The size and the potential for weight gain of the dog in this study could compromise its ambulation later, and it was a factor in the decision for the limb-sparing surgery. The allografts can be used to reconstruct the proximal femur, but they were not considered a viable option for this patient because of the reported complications, including graft fracture, non-union with the host bone and collapse of subchondral bone. The hip region does not allow the realization of arthrodesis because this joint is highly mobile, so the use of prosthetics as described is ideal for the preservation of joint biomechanics. Furthermore, the implant provides rapid postoperative recovery and immediate stability. Mean survival times were not significantly different between the limb-sparing and amputation techniques without adequate chemotherapy. In this case, despite the recommendation, the patient was monitored continuously without the association of adjuvant treatments according to the owner’s choice. The complications related with the use of cortical allograft, endoprosthesis, and pasteurized autograft include infection (31-60%), local recurrence (15-28%) or implant failure (11-40%). The implant luxation is the most common non-traumatic acute complication in the short term after limb-sparing surgery of proximal femur in humans and total hip replacement in dogs. To date, no complications have been observed after the procedure was performed. In conclusion, preservation of limbs in cases of osteosarcoma is favorable depending on the degree of involvement, but it requires specific techniques according to the location, to improve the quality of life and animal survival. In this case, the total hip arthroplasty for initial osteosarcoma in the femoral head and neck got an unexpected result, especially given the nature of osteosarcoma, limitations of wide excision with this approach and lack of adjuvant therapy.